A5.9 Influence of vitamin D status on cardiovascular involvement in systemic sclerosis. (13th February 2015) - Groseanu, L; Gudu, T; Balanescu, A; Predeteanu, D; Bojinca, V; Berghea, F; Saulescu, I; Opris, D; Borangiu, A; Constantinescu, C; Negru, M; Abobului, M; et al.
Abstract : Background: Cardiac involvement in systemic sclerosis is associated with poor prognosis and can be difficult to manage. Recent epidemiologic and experimental evidence has suggested that low vitamin D levels may play a role in cardiovascular conditions, including coronary artery disease, congestive heart failure, stroke and hypertension. Low vitamin D may lead to vascular smooth muscle cell proliferation, endothelial cell dysfunction, vascular and myocardial cell calcification, and increased inflammation. Objective: To evaluate the influence of vitamin D status in cardiovascular involvement in systemic sclerosis. Methods: 51 scleroderma patients were included in the study. Cardiac involvement was assessed by tissue Doppler imaging. 25(OH)D level was measured in the sera by an ELISA kit [DIASource ® 25-Hydroxyvitamin D Total ELISA assay (Nivelles, Belgium)]. 25(OH)D levels were considered normal for values ≥30 ng/ml, insufficient for values between 20–30 ng/ml and deficient for values under 20 ng/ml. Results: Patients with impaired vitamin D had higher sPAP than those with normal D levels (34.2 ± 14.33 vs. 25.25 ± 3.77, p = 0.008) and a trend for negative correlation between 25(OH)D and sPAP was identified (p = 0.053, r = -0.29). Patients with normal vitamin D levels did not have systolic or diastolic disfunction, rhythm or condunction disturbancies. Those patients with vitamin D deficiency had the highest frequencies of the above mentioned. Patients with vitamin D supplementation developed less rhythm and condunction disturbances than those without supplementation (p = 0.034). Negative correlations were identified between 25(OH)D levels and diastolic disfunction cu (p = 0.033, r = -0.318). An opposite variation was identified between 25(OH)D levels and right cardiac output, Anova test confirmed the differences between vitamin D subgroups (p = 0.001), but there was no correlation between parameters. 25(OH) level had a negative correlation with VTI_LVOT (velocity time integral left/right ventricular output) (p = 0.005, r = 0.663); an oppsosite variation was identified between vitamin D levels and left cardiac output and VTI_LVOT with significant differences between vitamin D subgroups confirmed by Anova test (p = 0.004, p = 0.001). There was also an opposite variation between 25OH)D levels and Et (early diastolic peak lateral mitral annular velocity) and At (late diastolic peak lateral mitral annular velocity), and in the same direction with Et/At ratio. Anova test validated differencies between subgroups: for Et (p = 0.039) and Et/At (p = 0.006). Conclusions: Vitamin D deficiency is associated with more severe cardiovascular involvement in systemic sclerosis. Our results suggest that patients with scleroderma might benefit from vitamin D supllementation, considering the fact that heart involvement in systemic sclerosis has no specific treatment.